TINJAUAN PSIKOLOGIS TENTANG KESEHATAN MENTAL ANAK - NASUTION, SAHADIR (IAIN Padangsidimpuan, 2013)
A soul has a very significant role in keeping this world alive. So, A soul needs a better guide based in his or her time. Children who have alive with no education of religion will always face doubts on their soulÂ even thoughÂ in their adult time they can think theoretically, they still normally do unexpected thing. But, the very important thing we must know that in doing shalat will take care of them alive.